Needle in fetal brain and its role in modern obstetrics: a case report - Rabab, Anushah; Agarwal, Anchal; Bhardwaj, Jagriti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Fetal hydrocephalus at term can obstruct labour and increase maternal risk, and although rarely employed in modern practice, cephalocentesis may decompress the fetal head and facilitate vaginal delivery. We describe two intrapartum transvaginal cephalocentesis procedures and consider their obstetric and ethical implications. In case 1, a 30-year-old multigravida at 38 weeks with Dandy–Walker malformation and severe hydrocephalus underwent transvaginal cephalocentesis with drainage of approximately 400 ml of cerebrospinal fluid (CSF), resulting in reduced biparietal diameter and uncomplicated vaginal delivery of a live infant who later required shunt placement. In case 2, a 27-year-old gravida 2 in labour with cord prolapse declined caesarean delivery and underwent cephalocentesis with drainage of about 200 ml CSF, enabling vaginal delivery of a stillborn infant, with uneventful maternal recovery. Although cephalocentesis is considered a destructive and infrequently indicated procedure, these cases highlight its continuing relevance in selected situations where maternal morbidity from caesarean delivery can be avoided and fetal prognosis is already poor owing to severe hydrocephalus and associated anomalies.